Mineralogy of the silt and clay fractions in Ultisols with darkened subsurface horizon in the state of Santa Catarina - Lunardi Neto, Antônio; Almeida, Jaime Antonio de (Revista de Ciências Agroveterinárias, 2013)
In the Santa Catarina state there occurs darkened subsurface horizon in Ultisols, whose morphology is similar to the sombric horizons of the Soil Taxonomy and FAO classification systems. But there are doubts about the possibility of there being buried horizons. The present study aimed to identify lithologic discontinuities in mineralogy of the silt and clay fractions of three Ultisols (red, yellow and brown-gray) which exhibit similar morphology to sombric horizons, located in the eastern region of Santa Catarina state. Samples were collected in the Ultisols from Içara, Rancho Queimado and Alfredo Wagner municipalities. In the samples TFSA proceeded to separate the silt and clay samples for analysis by X-ray diffraction (XRD), respectively analyzed in powder and oriented clay slides. Part of the clay samples, after removal of organic matter and the iron oxides was saturated with magnesium and saturated with ethylene glycol. After being analyzed by X-ray diffraction the samples saturated with magnesium underwent saturation with thylene glycol. The samples that were saturated with potassium were heated to various temperatures. The results identifi ed discontinuity clay mineralogy in Yellow and Brown-Gray Ultisols. These soils do not have sombric horizons. The Red Ultisol showed no mineralogical discontinuity and depend on further studies to confirm or not sombric horizon. The mineralogy of the clay sample indicated a predominance of kaolinite in all Ultisols, with significant amounts of vermiculite with hydroxyaluminum interlayered, gibbsite, illite and quartz. The silt sample showed only quartz. The soils have no detectable mineral reserve for plants.